Site-Dependent Relationships Between Fungal Community Composition, Plant Genotypic Diversity and Environmental Drivers in a Salix Biomass System - Hoeber, Stefanie; Baum, Christel; Weih, Martin; Manzoni, Stefano; Fransson, Petra (Frontiers in Fungal Biology, 2021)
Soil fungi are strongly affected by plant species or genotype since plants modify their surrounding environment, but the effects of plant genotype diversity on fungal diversity and function have not been extensively studied. The interactive responses of fungal community composition to plant genotypic diversity and environmental drivers were investigated in Salix biomass systems, posing questions about: 1) How fungal diversity vary as a function of plant genotype diversity; 2) If plant genotype identity is a strong driver of fungal community composition also in plant mixtures?; 3) How the fungal communities change through time (seasonally and interannually)?; and 4) Will the proportion of ECM fungi increase over the rotation? Soil samples were collected over four years starting pre-planting from two Salix field trials including four genotypes with contrasting phenology and functional traits, and genotypes were grown in all possible combinations (four genotypes in Uppsala, Sweden, two in Rostock, Germany). Fungal communities were identified using Pacific Biosciences sequencing of fungal ITS2 amplicons. We found some site-dependent relationships between fungal community composition and genotype or diversity level, and site accounted for the largest part of the variation in fungal community composition. Rostock had more homogenous community structure, with significant effects of genotype, diversity level and the presence of one genotype (‘Loden’) on fungal community composition. Soil properties and plant and litter traits contributed to explaining the variation in fungal species composition. The within-season variation in composition was of a similar magnitude to the year-to-year variation. The proportion of ECM fungi increased over time irrespective of plant genotype diversity, and in Uppsala the 4-mixture showed a weaker response than other combinations. Species richness was generally higher in Uppsala compared with that in Rostock and increased over time, but did not increase with plant genotype diversity. This significant site-specificity underlines the need of consideration of diverse sites to draw general conclusions on temporal variations and functioning of fungal communities. A significant increase in ECM colonization of soil under the pioneer tree Salix on agricultural soils was evident and points to a changed litter decomposition and soil carbon dynamics during Salix growth.